Varicella in COVID-19: A Case Report - Shrestha, Shree Krishna; Joshi, Arabind (Nepal Journal of Dermatology, Venereology & Leprology, 2021)
Coronavirus disease-2019 (COVID-19) is the viral pandemic with the propensity of having several systemic manifestations. As with other viral diseases, it has been associated with varied cutaneous manifestations and they range from maculopapular eruptions, vascular lesions to the chickenpox-like lesions. However, the co-occurrence of COVID-19 and varicella has been rarely reported.